The Impact of Humanity on The Social Life of the Muslim Ummah An Analytical Study - Prof. Dr Rohama Imran,; Ghulam Murtaza Soomro,; Nazar Hussain Chandio, (Al Manhal Research Journal, 2025)
The concept of human rights in Islam has a profound impact on the social life of the Muslim community (Ummah). Some of the effects include Promoting justice and equality: Islam emphasizes the equal value of all human life, regardless of race, gender, or social status. Protecting individual freedoms. Islamic teachings safeguard individual rights, such as freedom of worship, speech, and assembly. Encouraging compassion and empathy. Islam emphasis on human dignity and welfare fosters a sense of community and social responsibility. Islamic principles advocate for the protection and care of vulnerable groups, including women, children, and the poor. Fostering a sense of brotherhood and sisterhood, the concept of Ummah emphasizes unity and solidarity among Muslims, transcending geographical and cultural boundaries. Guiding social and economic policies, Islamic human rights principles inform social and economic policies, promoting fairness and justice in areas like trade, employment, and education. Empowering women and marginalized groups, Islamic teachings on human rights have been interpreted to promote women's rights, challenge patriarchal norms, and advocate for marginalized communities. Encouraging accountability and governance, the concept of human rights in Islam holds leaders and governments accountable for upholding justice, transparency, and the rule of law. Promoting education and awareness, Islamic human rights principles emphasize the importance of knowledge, education, and awareness in promoting social justice and human dignity. Inspiring social activism and reform, the Islamic concept of human rights has inspired social movements and reform efforts throughout history, advocating for justice, equality, and human dignity. By embracing human rights principles rooted in Islamic teachings, Muslim communities can cultivate a more just, compassionate, and equitable social life.